EFEKTIVITAS IKLAN DIGITAL GOOGLE ADSENSE - Alvita Tyas Dwi Aryani (Jurnal Ekonomi Dan Bisnis, 2017)
This study aimed  to test the effectiveness  of Google AdSense ads on your blog page using  Google Chrome and Firefox  browser.  Adsense display  is  said  to  be  effective if  AdSense ads  is  able to  display  a product  that  has previously  been  seen  on  the  Lazada  web  page.  Using  the  experimental  approach,  this  study  concluded  that effective AdSense looks good when viewed using Chrome or Firefox which in Chrome, users must sign in o rder to display AdSense effectively  while in Firefox it does not require such procedures. Keywords: Efektivitas  Tampilan Iklan Digital, AdSense, Chrome, Firefox, Lazada